2011
DOI: 10.1186/1471-2458-11-499
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association between all-cause mortality and multiple aspects of individual social capital among the older Japanese

Abstract: BackgroundFew prospective cohort studies have assessed the association between social capital and mortality. The studies were conducted only in Western countries and did not use the same social capital indicators. The present prospective cohort study aimed to examine the relationships between various forms of individual social capital and all-cause mortality in Japan.MethodsSelf-administered questionnaires were mailed to subjects in the Aichi Gerontological Evaluation Study (AGES) Project in 2003. Mortality da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(104 citation statements)
references
References 31 publications
11
92
0
Order By: Relevance
“…Helliwell and Putnam 15 analyzed the quality and quantities of community social networks using an index of "social capital (SC)", which is based on a fundamental concept encompassing "trust", "rules" and "networks" for promoting cooperative behavior among individuals. It was reported that SC was associated with mortality 12,16 , physical activity 17,18 , mental health 19 , and self-rated health 20e24 .…”
Section: Introductionmentioning
confidence: 99%
“…Helliwell and Putnam 15 analyzed the quality and quantities of community social networks using an index of "social capital (SC)", which is based on a fundamental concept encompassing "trust", "rules" and "networks" for promoting cooperative behavior among individuals. It was reported that SC was associated with mortality 12,16 , physical activity 17,18 , mental health 19 , and self-rated health 20e24 .…”
Section: Introductionmentioning
confidence: 99%
“…[65] There is also good evidence that mortality risks are lower among people who are 6 more socially integrated with higher levels of social cohesion. [13,17,[66][67][68][69][70] However, while there is a large body of research that suggests social cohesion is beneficial to health, associations are not necessarily consistent across studies. [71][72][73][74].…”
Section: Perceived Neighbourhood Cohesionmentioning
confidence: 99%
“…[70,[75][76][77][78][79][80][81] Social cohesion data are usually derived from cross-sectional surveys of health and social conditions. Other issues that may contribute to inconsistent evidence for associations between social cohesion and health include: different levels of measurement (individual, family or household, neighbourhood, city and country [69,79,[82][83][84][85]) and varied identification of relevant covariates. [70,[75][76][77][78][79][80][81] Each of these will be discussed in turn, starting with how social cohesion is conceptualised.…”
Section: Perceived Neighbourhood Cohesionmentioning
confidence: 99%
See 2 more Smart Citations